4 In 1 Tumbler / Auni Batrisyia Razilan … [et al.] - Razilan, Auni Batrisyia; Noorhisham, Batrisyia; Mohd Izan, Muhammad Haziq Auji; Mohd Nasir, Nur Nisa Awatif; Wee, Hassnah (Faculty of Computer and Mathematical Sciences, 2022)
Everyone's daily life necessitates a steady supply of water, especially in the summer. Furthermore, today's generation enjoys drinking various types of fresh juices. However, it is extremely difficult to prepare, especially when going on vacation. As a result, the 4 In 1 Tumbler a multifunctional tumbler, was created. The main goal of the4 In 1 Tumbler is to make it easier for people to bring it with them daily and to make it a useful item when going on vacation. People can use the 4 In 1 Tumbler instead of plastic cups to reduce their use of plastic, reducing harmful waste and preserving the environment for the future.